Discovery of a novel Keap1 inhibitor for neurodegeneration through virtual screening and molecular dynamics simulations - Md. Mazedul Hasan; Md. Shaki Mostaid; Asim Kumar Bepari; Hasan Mahmud Reza; Murad Hossain (PLoS ONE, 2026)
Oxidative stress is a key feature of Alzheimer’s disease (AD) and other neurodegenerative disorders. The Kelch-like ECH-associated protein 1 (Keap1)–nuclear factor erythroid 2–related factor 2 (Nrf2) pathway controls redox balance, and disrupting the Keap1–Nrf2 protein–protein interaction (PPI) has become a promising therapeutic approach. Marine natural products (MNPs), because of their structural diversity and bioactivity, are an underexplored source of potential neuroprotective compounds. This study aimed to identify novel marine-derived inhibitors of the Keap1–Nrf2 interaction using a comprehensive in silico pipeline. A total of 14,492 compounds from an open-access MNP database were virtually screened against the Keap1 Kelch domain through molecular docking. The top 1,329 candidates exhibited strong binding affinities, with several reaching scores comparable to the co-crystallized reference ligand L5F. Absorption, distribution, metabolism, excretion, and toxicity (ADMET) profiling was employed to assess pharmacokinetic properties, brain penetration, and safety, leading to the identification of compound 145398-61-4 as the most promising hit. Molecular dynamics (MD) simulations verified the structural stability of the Keap1–145398-61-4 complex, while binding free energy calculations indicated energetically favorable interactions. Additional validation using principal component analysis (PCA) and highest occupied molecular orbital–lowest unoccupied molecular orbital (HOMO–LUMO) energy analysis further confirmed the stability of this interaction. Overall, our in silico study identified compound 145398-61-4 as a novel Keap1–Nrf2 inhibitor, highlighting its potential as a lead candidate for developing treatments for Alzheimer’s disease and other neurodegenerative disorders, such as amyotrophic lateral sclerosis and multiple sclerosis.